2005
DOI: 10.1590/s0100-72032005001000002
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus agalactiae em gestantes: prevalência de colonização e avaliação da suscetibilidade aos antimicrobianos

Abstract: Objetivos: verificar a ocorrência de colonização por Streptococcus agalactiae em gestantes e avaliar a suscetibilidade das amostras isoladas aos antimicrobianos. Métodos: foram avaliadas 167 grávidas entre a 32 a e a 41 a semana de gestação, independente da presença ou não de fatores de risco, atendidas no ambulatório de pré-natal entre fevereiro de 2003 e fevereiro de 2004. O material vaginal/anal, colhido com um único swab, foi inoculado em caldo Todd-Hewitt acrescido de ácido nalidíxico (15 μg/mL) e gentami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
1
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 19 publications
(16 reference statements)
3
10
1
9
Order By: Relevance
“…This worldwide variability is related to different sociocultural, geographic, climatic, biological and methodological determinants. Brazilian studies have found rates ranging from 5 to 25% (3,5,22,23,26,29,30). Our finding of a 32.6% rate of GBS prevalence using the genetic detection directly from the enrichment culture is worrisome and the highest reported in the country to our knowledge so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This worldwide variability is related to different sociocultural, geographic, climatic, biological and methodological determinants. Brazilian studies have found rates ranging from 5 to 25% (3,5,22,23,26,29,30). Our finding of a 32.6% rate of GBS prevalence using the genetic detection directly from the enrichment culture is worrisome and the highest reported in the country to our knowledge so far.…”
Section: Discussionmentioning
confidence: 99%
“…As the culture-PCR based method, in our study, showed higher GBS detection rates, and two genetic markers were targeted, we believe that Although vancomycin is not a first line drug for prophylaxis of perinatal streptococcal disease, some enterococci and Staphylococcus aureus (28) isolates have been proving resistant to this antibiotic. This trend notwithstanding, no vancomycin-resistant GBS isolates have been identified (2,5,10,24,28). In the light of the findings, vancomycin may be considered a better option for prophylaxis of patients allergic to penicillin.…”
Section: Discussionmentioning
confidence: 99%
“…19 In Rio de Janeiro prevalence rates of 19.2% were found from 2003 to 2004. 20 A study accomplished at the Center for Integral Attention to Women's Health at the University of Campinas in 2003 and 2004 found the rate ofmaternal GBS colonization of 27.6%. 6 In São Luis -Maranhão, the prevalence was 20.4% from 2005 to 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Erythromycin and clindamycin are the drugs of choice for prophylaxis in women colonized by GBS who are allergic to penicillin. 1 Although most strains are susceptible to penicillin, 14,15,20,23,24 the increased use of erythromycin and clindamycin in patients allergic to penicillin or for the prevention and treatment ofother infections, has shown growth rates of GBS resistance to these antimicrobial agents in many countries, including Brazil. 15,20 A study made from 1994 to 1999 in Rio de Janeiro found in colonized women 5.4% and 1.1% of GBS resistance to erythromycin and clindamycin, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation